Correlation between the Neutrophil-to-Lymphocyte Ratio and Multiple Sclerosis: Recent Understanding and Potential Application Perspectives - Qingqing Zhou; Rui Jia; Jingxia Dang (Neurology Research International)
Multiple sclerosis (MS) is a chronic debilitating immune-mediated disease of the central nervous system, which causes demyelination and neuroaxonal damage. Low-grade systemic inflammation has been considered to lead to pathogenesis owing to the amplification of pathogenic immune response activation. However, there is a shortage of reliable systemic inflammatory biomarkers to predict the disease activity and progression of MS. In MS patients, a series of cytokines and chemokines promote the proliferation of neutrophils and lymphocytes and their transfer to the central nervous system. The neutrophil-to-lymphocyte ratio (NLR), which combines the information of the inherent and adaptive parts of the immune system, represents a reliable measure of the inflammatory burden. In this review, we aimed to discuss the inflammatory response in MS, mainly the function of lymphocytes and neutrophils, which can be implemented in the utility of NLR as a diagnostic tool in MS patients. The underlying pathophysiology is highlighted to identify new potential targets for neuroprotection and to develop novel therapeutic strategies.